2022
DOI: 10.1075/ap.00006.sch
|View full text |Cite
|
Sign up to set email alerts
|

Teaching L2 pragmatics to young learners

Abstract: This paper reviews research on teaching pragmatics – and more specifically speech acts – to young L2 learners from two perspectives: (1) studies investigating young L2 learners’ pragmatic competence and (2) studies examining the potential of different materials with regard to pragmatics instruction. The review of L2 learners’ speech act competence addresses cross-sectional and longitudinal developmental studies, as well as studies that examined the effects of specific instructional approaches, learning context… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…This can be partly due to the nature of SA programs, which require individuals to spend a considerable period away from their families and home countries. Yet, as the literature suggests, this is not only the case for SA research, and in general, studies on young learners' pragmatic competence and development have not received due attention (Alemi and Haeri 2020;Schauer 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be partly due to the nature of SA programs, which require individuals to spend a considerable period away from their families and home countries. Yet, as the literature suggests, this is not only the case for SA research, and in general, studies on young learners' pragmatic competence and development have not received due attention (Alemi and Haeri 2020;Schauer 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the previous studies revealed that intrinsic or communication-oriented motivation helps individuals to use more appropriate pragmatic forms, have a greater awareness of L2 pragmatics, and better identify pragmatic errors (Tagashira et al 2011;Takahashi 2015;Tajeddin and Zand Moghadam 2012). However, so far, some variables such as learners' age or gender and their role in their pragmatic development have received less attention (Schauer 2022;Tajeddin and Malmir 2014) The findings from the studies reviewed above have contributed to our understanding of pragmatic acquisition and provided a lens to see how learner variables are implicated in this acquisition. However, despite the rich literature on SA as well as various reviews on pragmatic instruction and the roles of different variables on learners' achievements (e.g., Barron 2019;Nightingale and Alcón-Soler 2023;Wyner and Cohen 2015;Xiao 2015b), no systematic review has yet specifically targeted the interplay of learners' variables, including their cognitive, affective, personal, and psychological ones, with their pragmatic development during their SA programs.…”
Section: Learner Variables In Pragmatic Acquisitionmentioning
confidence: 99%